Milrinone: An advancement in the treatment of Alzheimer's Disease - Tariq, Hemaila; Ahmed, Bilal; Hafiz, Muhammad Yusuf (Journal of the Pakistan Medical Association, 2022)
Alzheimer’s Disease (AD) is a complex neurodegenerative disease with a progressive degeneration of behavioral and cognitive functions such as memory. [1] Alzheimer's disease is characterized by amyloid-B plaques, tau protein hyperphosphorylation, microglial cell activation and release of inflammatory cytokines such as IL-1B leading to disease progression. Amyloid-B plaques act on Toll-like receptors on microglial cells, thereby activating them and causing the release of pro-inflammatory cytokines. [2] Milrinone is a Phosphodiesterase inhibitor that has vasodilatory effects in the vasculature and has shown to suppress neurocytes apoptosis and inflammation. [3]. A study performed on APP/PSI transgenic mice demonstrated that milrinone reduces formation of amyloid-B plaques, suppresses tau protein hyperphosphorylation and release of inflammatory cytokines and reduces neuroinflammation therefore improving memory and cognitive functioning and helps reduce the progression of Alzheimer’s disease.[4] As per recent statistics, low-middle income countries constitute 58% of the world's aging population and this is expected to reach 68% by 2050. China, South Asian countries including Pakistan and Western pacific neighbors have reported the fastest growth in their geriatric population (5). In Pakistan, a country of approximately 220 million people with an increasing elderly population, there are very limited dementia trained specialists and available treatment options (6). Milrinone, a drug conventionally being used in cardiovascular treatments, could help bridge this gap and allow us to cater to the increasing burden of Alzheimer’s disease in Pakistan.